Promoting Local Innovation : Enhancing IK Dynamics and Links with Scientific Knowledge - World Bank (Washington, DC, 2012)
Local innovation refers to the dynamics of IK - the knowledge that grows within a social group, incorporating learning from own experience over generations but also knowledge gained from other sources and fully internalized within local ways of thinking and doing. Local innovation is the process through which individuals or groups discover or develop new and better ways of managing resources - building on and expanding the boundaries of their IK.